Older people during the COVID-19 Pandemic: public policies and access to information and communication technologies in Argentina - Pochintesta, Paula Analía (2021)
The elderly are part of a society defined by technology acceleration, communication and information. These transformations happen at a rapid pace, making a big impact in the life of senior citizens. Our premise is to consider older people as active subjects in full exercise of their rights, to whom digital inclusion is also a part of social inclusion. The objective of this paper is, on the one hand, to carry out a content analysis of the policies implemented in Argentina regarding digital inclusion, including: level of coverage and survey of possible existing gaps. On the other hand, data from a national survey on access to resources and use of information and communication technologies by the elderly are analyzed. The conclusions show that there are significant gaps in both access to resources and frequency of use. Regarding national public policies on the subject, we observed that the pandemic showed that there was no strategic plan for the achievement of a policy of inclusion of the elderly in the new technologies.